Route Optimisation and Expansion of BisKita Depok Service Corridor using Set Covering Problem Approach - Prasetya, A.B.; Zulkarnain; Laoh, E. (South African Journal of Industrial Engineering, 2025)
Sustainable transportation is crucial for Indonesia to support urban development and to reduce carbon emissions. Depok, a satellite city of Jakarta, faces problems such as traffic congestion and reliance on private vehicles. In July 2024, the government launched the BisKita Depok service to improve public transport accessibility and to reduce emissions, aligning with Sustainable Development Goals 11 and 13. Using the set cover problem model, this study optimises bus routes to expand their coverage and operational efficiency. The findings recommend strategies to establish BisKita Depok as a sustainable transportation model for other cities and provide actionable insights for reducing national carbon emissions.